Diagnostic value of abdominal CT scan in ovarian tumors in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2017 to December 2018 - Ida Bagus Gede Ramayuda; Lies Mardiyana; Dyah Erawati; Indra Yuliati (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHTS1. Ovarian tumors diagnostic value has been determined using the tools on contrast-enhanced abdominal CT Scan.2. The tools including primary finding like mass size, septation, solid component, and additional finding such as ascites, peritoneal implants, lymph node enlargement.3. Most tumors were ovarian malignant tumors according to their histopathological results.4. Contrast-enhanced abdominal CT Scan of ovarian tumors evaluated by the tools gave better and more reliable diagnostic value than without using the tools.ABSTRACTObjectives: The purpose of this study was to determine the diagnostic value of contrast-enhanced abdominal CT scan in ovarian tumors in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, to provide scientific and clinical benefits.Materials and Methods: Samples were taken retrospectively by contrast-enhanced abdominal CT scan raw data in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January 2017 to December 2018. Using inclusion and exclusion criteria, a total of 88 samples were obtained and reviewed blindly by Female Organ Division of Radiology Department, Faculty of Medicine Universitas Airlangga, and by using "tools" (primary and additional findings of modified ovarian tumors malignancy). The data were correlated with histopathological findings and analyzed by statistical tests and the results with and without "tools" were compared.Results: Samples were grouped by age, distributed with a range of 20 years and the group of 41-60 years had the highest age of ovarian tumor samples (46.6%) with 84.1% being ovarian malignant tumors according to their histopathological results. It was dominated by serous, mucinous and endometroid types with sensitivity of 93.3%, specificity of 64.3%, positive predictive value of 93.3% negative predictive value of 69.2%, and accuracy value of 89.8%. More reliable results were obtained by using “tools”.Conclusion: Contrast-enhanced abdominal CT scan of ovarian tumors in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, evaluated by “tools” still had a better and more reliable diagnostic value than without tools in determining policy steps in handling ovarian tumors with a note that more in-depth research on pitfalls is needed so it may enrich the characteristic findings in imaging.